Human Milk Short-Chain Fatty Acid Composition is Associated with Adiposity Outcomes in Infants. Issue 5 (3rd May 2019) - Prentice, Philippa M; Schoemaker, Marieke H; Vervoort, Jacques; Hettinga, Kasper; Lambers, Tim T; van Tol, Eric A F; Acerini, Carlo L; Olga, Laurentya; Petry, Clive J; Hughes, Ieuan A; Koulman, Albert; Ong, Ken K; et al.
ABSTRACT: Background: Presumed benefits of human milk (HM) in avoiding rapid infancy weight gain and later obesity could relate to its nutrient composition. However, data on breast milk composition and its relation with growth are sparse. Objective: We investigated whether short-chain fatty acids (SCFAs), known to be present in HM and linked to energy metabolism, are associated with infancy anthropometrics. Methods: In a prospective birth cohort, HM hindmilk samples were collected from 619 lactating mothers at 4–8 wk postnatally [median (IQR) age: 33.9 (31.3–36.5) y, body mass index (BMI) (kg/m 2 ): 22.8 (20.9–25.2)]. Their offspring, born at 40.1 (39.1–41.0) wk gestation with weight 3.56 (3.22–3.87) kg and 51% male, were assessed with measurement of weight, length, and skinfold thickness at ages 3, 12, and 24 mo, and transformed to age- and sex-adjusted z scores. HM SCFAs were measured by 1 H-nuclear magnetic resonance spectroscopy (NMR) and GC-MS. Multivariable linear regression models were conducted to analyze the relations between NMR HM SCFAs and infancy growth parameters with adjustment for potential confounders. Results: NMR peaks for HM butyrate, acetate, and formic acid, but not propionate, were detected. Butyrate peaks were 17.8% higher in HM from exclusively breastfeeding mothers than mixed-feeding mothers ( P = 0.003). HM butyrate peak values were negatively associated with changes in infant weight (standardized B = −0.10, P = 0.019) and BMI ( B = −0.10, P = 0.018) between 3 and 12 mo, and negatively associated with BMI ( B = −0.10, P = 0.018) and mean skinfold thickness ( B = −0.10, P = 0.049) at age 12 mo. HM formic acid peak values showed a consistent negative association with infant BMI at all time points (B < = −0.10, P < = 0.014), whereas HM acetate was negatively associated with skinfold thickness at 3 mo ( B = −0.10, P = 0.028) and 24 mo ( B = −0.10, P = 0.036). Conclusions: These results suggest that HM SCFAs play a beneficial role in weight gain and adiposity during infancy. Further knowledge of HM SCFA function may inform future strategies to support healthy growth.